Early detection relationship of cerebral palsy markers using brain structure and general movements in infants born <32 weeks gestational age. (December 2021) - Wang, Jun; Shen, Xiushu; Hu, Xihong; Yang, Hong; Yin, Huanhuan; Zhu, Xiaoyun; Gao, Herong; Wu, Yun; Meng, Fanzhe
Abstract: Aim: To detect early brain structural and clinical functional markers of brain injury and development based on a magnetic resonance imaging (MRI) scoring system and a general movement assessment (GMA) for preterm infants later diagnosed with cerebral palsy (CP). Study design: Retrospective cohort study. General movements (GMs) were scored according to a semiquantitative scoring system: the GMs optimality score (GMOS) at preterm and term ages and the Motor Optimality Score (MOS) at the corrected age of 3 months after birth. Brain magnetic resonance imaging (MRI) at term-equivalent age was scored using an MRI scoring system. We analyzed the relationship between the early degree of cerebral white matter (WM) abnormality and the GMOS and the MOS for infants born <32 weeks gestational age later diagnosed with CP in a comparison group of neurotypical controls. Subjects: Sixteen preterm infants were included in this study who underwent MRI and GMs assessment. 8 out of the 16 preterm infants were later diagnosed with CP, while the other 8 infants with normal motor development (N) were placed into the control group. Their median gestational age was 30w6d and 27w6d for each group respectively. Results: The cerebral WM MRI scores were significantly higher in the CP group than in the control group ( p  < 0.01). The GMOS and MOS were significantly higher in the control group than in the CP group ( p  < 0.05). The MOS showed a strong correlation to the cerebral WM MRI score ( r  = -0.88) and the subscale of cerebral WM items (the cystic degeneration and the focal signal abnormalities) of the MRI score ( r  = -0.94) in the CP group. The MOS also showed a correlation with corrected biparietal diameter (cBPD) in the preterm infant group with CP ( r  = 0.75). Results of linear regression analyses between term MRI and GMs measures in preterm infants with CP are presented. Cerebral WM scores were associated with the MOS (β = −0.63; 95%CI = −0.97, −0.29; p  < 0.01). Cerebral WM injury, including the subscale of cystic degeneration and focal signal abnormalities was closely associated with the MOS (β = −0.83; 95%CI = −1.13, −0.54; p  < 0.001). Conclusion: Cerebral WM scores show a strong association with a decreased motor performance on the MOS in preterm infants later diagnosed with CP. Severe white matter injury and significantly decreased MOS scores may provide useful early markers and strong evidence to early predict the risk of later development of cerebral palsy in preterm infants. Highlights: MRI and GMs are used to identify structural and functional markers of brain injury and development. Cerebral WM scores show a strong association with a decreased motor performance on the MOS. White matter injury and MOS are early markers for later development of cerebral palsy in preterm infants.